The Effect of Investment Knowledge, Perception of Benefits, Perception of Risk, Minimum Capital on Interest in Investing in the Islamic Capital Market with Income as Moderating Variable (Universitas Negeri Semarang, 2022)
The purpose of this study was to analyze the role of income in moderating the effect of investment knowledge, perceived benefits, perceived risk and minimal capital on interest in investing in the Islamic capital market. The method used a quantitative approach with a sample of 100 students from the Faculty of Economics and Business (FEB) State Universities in Surabaya, namely Universitas Islam Negeri Sunan Ampel Surabaya, Universitas Negeri Surabaya and Universitas Airlangg. This research data was collected by using a questionnaire distributed online in the form of a google form. The data obtained in this research was processed by using the SPSS 25 program. Meanwhile, to measure the moderating variable, the moderated regression analysis (MRA) test was used. This research concluded that investment knowledge, perceived benefits, the perception of risk and minimal capital had a positive and significant effect on interest in investing in the Islamic capital market. In addition, income moderated investment knowledge, perceived benefits, perceived risk and minimal capital on interest in investing in the Islamic capital market.